Ultrasound evaluation of common carotid artery blood flow in the Labrador retriever - Svicero, Denis J. [UNESP] (2013)
Background: Doppler ultrasound (DUS) examination provides quantitative and qualitative information concerning the blood flow in veins and arteries, enabling their morphological evaluation and the collection of hemodynamic data. Dogs and cats as well as humans may display neurological signs of brain hypoperfusion secondary to common carotid alterations. Hence, DUS examination might aid in the differential diagnosis of neurological disorders of ischemic origin, among other causes. The objective of this study was to register normal values for systolic peak velocity, minimum diastolic velocity, diameter and resistance index of both common carotid arteries of 12 healthy Labrador retriever dogs between 2 and 5 years of age. By gathering these values, we might be able to improve the sensitivity of hemodynamic studies in clinically important brain disorders. Results: There were no statistical differences between the values for the right and left vessels: the systolic peak velocity was 75.8 ± 16 cm/s, minimum diastolic velocity was 12.2 ± 4 cm/s, common carotid diameter was 0.545 ± 0.063 cm, and resistance index was 0.83 ± 0.07. Conclusions: The results of this study might be used to establish normal parameters for Labrador retriever dogs and thus help in the diagnosis of neurological disorders associated with alterations of the carotid arteries. Similar studies must be performed to evaluate the same parameters in other dog breeds of different sizes and skull conformations. © 2013 Svicero et al.; licensee BioMed Central Ltd.